АНАЛИЗ ПОКАЗАТЕЛЕЙ КАЧЕСТВА ЖИЗНИ У ПАЦИЕНТОВ С НЕДИФФЕРЕНЦИРОВАННОЙ ДИСПЛАЗИЕЙ СОЕДИНИТЕЛЬНОЙ ТКАНИ - Н. Ю. Кононова; И. Л. Иванова; Т. Е. Чернышова (Архивъ внутренней медицины)
The article discusses the quality of life in patients with undifferentiated dysplasia of connective tissue, obtained by «SF-36 Health Status Survey», assessment of anxiety along “The Scale of assessment of the level of reactive and personal anxiety” and General psychological state on the questionnaire “Health, activity, mood”.